Knowledge, attitude and practice towards the implementation of outcome-based education among the academics in Universiti Putra Malaysia - Mohamad, Siti Fatimah; Ungku Zainal Abidin, Ungku Fatimah; Saari, Nazamid; Zakaria, Muta Harah; Ismail, Alyani; Man, Nor Azirawani (Blue Eyes Intelligence Engineering & Sciences Publication, 2019)
Numerous efforts have been taken to prepare graduates for employment right after their graduations. The statistics show that over 53,000 of Malaysian graduates were unemployed in 2017 and expected to increase in 2018 as the total unemployment for all group of people in July 2018 was 518,600. Although the outcome-based education (OBE) has been advocated in the 1970s to improve students’ achievement, higher education institutions are still struggling to produce quality and capable graduates to the industry. As the new education systems are emerging from time to time, academics of higher education institutions might have different interpretations of outcome-based education and its practices. Therefore, this study was conducted to identify the level of knowledge, attitude, and practice (KAP) relating to the OBE among academics in Universiti Putra Malaysia and to compare the respondents’ work profile characteristics with the KAP towards the implementation of the OBE. A total of 173 academics participated in this study through an online survey. The findings of this study indicated that the majority of the respondents were well versed with the knowledge of OBE and have a positive attitude and practices towards the implementation of OBE. Next, the results show that there are significant differences between positions on the respondents’ knowledge, and for the year of service in UPM on respondents’ attitude and practices towards the OBE implementation. It is anticipated that the findings from this study may help the university to improve the OBE system and to prepare the academics with the right knowledge, attitude, and practice towards the OBE implementation.